2020
DOI: 10.21203/rs.3.rs-17593/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic analysis of the Capsicum ERF transcription factor family: identification of regulatory factors involved in the regulation of species-specific metabolites

Abstract: Abstract Background: ERF transcription factors (TFs) belong to the Apetala2/Ethylene responsive Factor (AP2/ERF) TF family and play a vital role in plant growth and development processes. Capsorubin and capsaicinoids have relatively high economic and nutritional value, and they are specifically found in Capsicum. However, there is little understanding of how ERFs participate in the regulatory networks of capsorubin and c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…In fleshy fruits such as tomatoes and watermelon, high levels of the carotenoid lycopene accumulate, and early steps in the lycopene synthesis pathway are upregulated, but late cyclization is restricted (Fraser et al ., 2002). In the fruits of red pepper, the content of the major chloroplast pigment lutein decreases during the ripening process from its highest level during the nonripe stage, whereas the levels of β -carotene gradually increase, and other β -carotenoids, including β -cryptoxanthin, zeaxanthin, and capsanthin, begin to be synthesized de novo (Rodriguez-Uribe et al ., 2012; Song et al ., 2020). In this study, in pepper fruit, accumulation of the major ripening pigment capsanthin was found to be associated with fruit development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fleshy fruits such as tomatoes and watermelon, high levels of the carotenoid lycopene accumulate, and early steps in the lycopene synthesis pathway are upregulated, but late cyclization is restricted (Fraser et al ., 2002). In the fruits of red pepper, the content of the major chloroplast pigment lutein decreases during the ripening process from its highest level during the nonripe stage, whereas the levels of β -carotene gradually increase, and other β -carotenoids, including β -cryptoxanthin, zeaxanthin, and capsanthin, begin to be synthesized de novo (Rodriguez-Uribe et al ., 2012; Song et al ., 2020). In this study, in pepper fruit, accumulation of the major ripening pigment capsanthin was found to be associated with fruit development.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen pericarp tissues were freeze-dried for 24 h with a freeze dryer (Labconco/Freezone, Labconco, America) and ground into fine powder by an A 11 basic analytical mill (IKA, Germany). The extraction of pepper carotenoids was performed as described previously (Song et al ., 2020) with some modifications. Briefly, a total of 0.5 g of the freeze-dried samples was added to 8 ml of extracting solution containing hexyl hydride, acetone and absolute ethyl alcohol (2:1:1, HPLC grade), and then the samples underwent ultrasonic-assisted extraction for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of TF family members, such as MYBs [63], ERFs [64] and WRKYs [65], has been widely performed in many plants and has contributed to identifying gene functions. Several TF families have already been identified and systematically investigated for their functions in growth and development processes in tea plant; these families include the HSP gene superfamily [66], the VQ gene family [67] and the GRF and GIF gene families [68].…”
Section: Discussionmentioning
confidence: 99%
“…4). Numerous studies have reported that MYC2 usually regulates alkaloids biosynthesis by interacting with ERF TFs [41][42][43], and ERF TFs are associated with capsaicinoid biosynthesis in Capsicum [34,67]. MYC2 was mapped to two homologous genes, CabHLH006 and CabHLH018 that were classi ed into cluster L8 and cluster L7, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[15,[21][22][23][24][25][26][27][28][29][30]. Although WRKY, NAC and AP2/ERF TF families have been analysed systematically in peppers [31][32][33][34], genome-wide identi cation of the bHLH family has still not been reported. bHLH TFs are closely related to the primary and specialized metabolites of the plant.…”
mentioning
confidence: 99%